2010
DOI: 10.4314/njm.v19i4.61964
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude and leading causes of in-hospital mortality at Aminu Kano Teaching Hospital, Kano, northern Nigeria: A 4-year prospective analysis

Abstract: Background: Population based mortality data are scarce especially in developing countries including Nigeria. Despite its limitations, hospital mortality analysis assesses the quality of health-care delivery and provides a proximate measure of mortality. We reviewed the magnitude and causes of death among in-patients in a tertiary hospital in northern Nigeria. Methods: Analysis of mortality rate and causes of death for the period 20052008 (inclusive) in Aminu Kano Teaching Hospital. Causes of death were prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
36
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(49 citation statements)
references
References 2 publications
9
36
3
1
Order By: Relevance
“…In a study by Ezegwui et al [5], where only 6.2% of the patients were satisfied with the cost of services, cost was also noted as a major dissatisfaction area. However, some other researchers [6,9] have reported higher satisfaction levels in contrast to our findings.…”
Section: Perception Of Eye Care Deliverycontrasting
confidence: 56%
See 2 more Smart Citations
“…In a study by Ezegwui et al [5], where only 6.2% of the patients were satisfied with the cost of services, cost was also noted as a major dissatisfaction area. However, some other researchers [6,9] have reported higher satisfaction levels in contrast to our findings.…”
Section: Perception Of Eye Care Deliverycontrasting
confidence: 56%
“…Despite these challenges 79.5% of the participants were generally satisfied with the services provided by the hospital. Other researchers [5,6,9] have reported even higher levels of general satisfaction. Of the participants who have visited other hospitals for eye care, 80.4% feel our treatment is more effective, 73.2% feel our staff are more proficient and 73.2% feel our staff have better attitude.…”
Section: Perception Of Eye Care Facilitymentioning
confidence: 96%
See 1 more Smart Citation
“…Problemy związane z transplantacją związane są w głównej mierze z małą popularnością i traktowaniem jej jako tematu tabu oraz z dysproporcji stosunku biorców do dawców, których liczba przewyższa liczbę osób deklarujących oddanie narządów [4]. Nie tylko w Polsce, ale i na świecie liczba dawców jest niewystarczająca i wg dostępnych danych jest mniejsza niż liczba zadeklarowanych dawców, pomimo zwiększonej liczby deklaracji woli oddania organów po śmierci [4,[8][9][10]. Istotne znaczenie w zmianie postrzegania tej formy pomocy ma edukacja i uświadamianie społeczeństwa, a w tym poznanie motywów, którymi kierują się dawcy i ich najbliżsi w podejmowaniu tej trudnej decyzji [4].…”
Section: Wstępunclassified
“…2 The WHO South-East Asia Region has the second highest rate (251•3 per 10 000 livebirths), whereas the rate in the WHO Americas Region is only 3•7 per 10 000 livebirths. Several hospital-based studies [3][4][5][6] have shown that severe hyperbilirubinaemia contributes substantially to neonatal morbidity and mortality worldwide. According to two 2017 reports, 7,8 19•4% and 9•0% of the deaths at two Nigerian facilities were due to jaundice and acute bilirubin encephalopathy, respectively.…”
Section: Introductionmentioning
confidence: 99%